Revisiting zakat distribution in the modern era: Toward a reconstructed model - Aziz, Abdul; Faruk, Faruk (al-Uqud : Journal of Islamic Economics, 2025)
The distribution of charity to mustahik (zakat recipients) initially followed a personal and traditional consumer-based model, typically through the direct provision of daily necessities in the form of wealth donations. Most scholars emphasize the requirement of tamlik (transfer of ownership) when distributing zakat. In the contemporary era, BAZ (Badan Amil Zakat) and LAZ (Lembaga Amil Zakat) evolved their distribution methods through programs that include not only the transfer of wealth but also non-material forms, such as education, healthcare, empowerment, and social or da'wah initiatives. This study employs a qualitative case study approach, aiming to examine the reconstruction of charity distribution comprehensively and deeply from the perspective of contemporary Islamic law and social change. The research findings indicate a shift in distribution patterns from traditional consumer models to more creative and productive models. These are implemented through various programs, including scholarship schemes, health services, and economic empowerment initiatives. Additionally, the scope of Sabilillah beneficiaries has expanded to include incentives for TPQ (Qur'anic education) teachers, Qur'an memorizers, and training for future preachers. These transformations reflect an effort to adapt zakat distribution to current societal needs through a process of accommodation.